Reducing Premarital Sexual Behavior Through Information Services with the Pancawaskita Approach for Class X PL Students of SMK Negeri 4 Medan - Batu Bara, Khoiriah; Deliati, Deliati; Magdalena, Magdalena (Lembaga Riset Mutiara Akbar, 2025)
Premarital sexual behavior among adolescents has become an increasingly concerning issue, particularly in Vocational High Schools (SMK). This study aims to reduce students’ tendency toward such behavior through information services using the Pancawaskita approach, implemented among tenth-grade students of SMK Negeri 4 Medan. The research employed the Guidance and Counseling Action Research (PTBK) method, conducted in two cycles. The results showed a significant increase in students' understanding and self-control regarding the risks of premarital sex. Prior to the intervention, only 35% of students demonstrated a high level of understanding; after the second cycle, this figure rose to 82%. The Pancawaskita approach, which emphasizes the development of (cognition), (emotion), (intention), (action), and spiritual devotion, proved effective in fostering students’ awareness and commitment to maintaining morally responsible and healthy behavior.